'Please Send Us Your Money': The BBC's Evolving Relationship With Charitable Causes, Fundraising and Humanitarian Appeals. Issue 4 (2nd October 2018) - Franks, Suzanne
Abstract : Fundraising for charitable causes has had a key place in the BBC's schedule since the earliest days of the corporation and the establishment of the weekly radio appeal. As new forms of fundraising through high-profile media events developed in the 1980s, raising unprecedentedly large sums for charity, the BBC had to adjust the way it negotiated with good causes and audiences. These changes coincided with professionalization and rapid growth of the NGO sector, which sought to elicit funds from a wider public using innovative techniques and new ways of reaching out through the media. This article uses internal BBC documents to examine how, against this rapidly changing background, the organization navigated the rules behind broadcasting of appeals. This includes the way that the BBC interacted with the Disasters Emergency Committee that had been established in the 1960s to provide an interface between broadcasters and charities to oversee exceptional fundraising for international causes. In some cases, the BBC faced difficulties in reconciling its duty to educate audiences about charitable causes with the fundraising imperative which relied on TV extravaganzas. In other cases, the BBC confronted the question of whether it was hosting a global fundraising event or simply covering an event organized by others. These kinds of emerging challenges which arose out of new innovations in fundraising via broadcasting produced interesting debates that are still evolving both within the charitable sector and in the way it relates to the media. The BBC's role within this ecology provides some illuminating insights about the issues connected with raising funds for humanitarian causes.